Orographic rainfall hot spots in the Andes‐Amazon transition according to the TRMM precipitation radar and in situ data - Chávez Jara, Steven Paul (2017)
The Andes‐Amazon transition, along the eastern Peruvian Andes, features “hot spots” with strong precipitation. Using 15 years of Tropical Rainfall Measuring Mission PR data we established a robust relation between terrain elevation and mean surface precipitation, with the latter peaking around 1000 m above sea level (asl), coinciding with the moisture flux peak of the South American Low Level Jet (SALLJ). There is strong diurnal variability, with afternoon (13–18 LT) convection in the Amazon plains, while on the eastern slopes (1000–2000 m asl), after the forcing associated with the thermal heating of the Andes subsides, convection grows during the night and surface precipitation peaks around 01–06 LT and organizes into mesoscale convective systems (MCSs). These then displace downslope to an terrain elevation of 700 m asl with stratiform regions spreading upslope and downslope and then decay during the remainder of the morning. The large MCSs contribute with at least 50% of daily rainfall (60% of the 01–06 LT rainfall). On synoptic scales, the large MCSs are more common in stronger SALLJ conditions, although subtropical cold surges are responsible for 16% of the cases.